Firewood usage and indoor air pollution from traditional cooking fires in Gazi Bay, Kenya. (6th February 2019) - Jung, Julia; Huxham, Mark
Abstract: Mangroves are increasingly being recognised for the important ecosystem services they provide, including carbon fixation, shoreline protection and fisheries habitats. In addition, they provide typical forest goods such as timber and firewood; harvesting these can cause forest degradation and loss. In Kenya, a large proportion of the rural population cook using firewood on traditional, inefficient three-stone fires. Although harvesting mangrove wood is illegal, the high poverty rate, absence of alternative fuels and lack of law enforcement mean it is likely to remain widespread, with consequent pressure on the forests. The use of three-stone fires has been associated with high levels of indoor air pollution, causing adverse health impacts. The current project aimed to determine a baseline of wood usage and health burden caused by indoor air pollution at a mangrove dependent community in Gazi Bay, southern Kenya. Basic information about fuel usage and perceived health problems related to indoor air pollution was collected using a questionnaire. Wood usage patterns were recorded for 28 days to establish the average daily wood consumption and main species used. Passive diffusion tubes were used to assess CO concentrations over 24 hours. Particulate pollution for the size fraction PM2.5 was measured during cooking using a DustTrak aerosol monitor. Mean daily per capita wood consumption was 1.2 kg although this varied significantly depending on household size, with larger households using less per capita wood. The mangrove Rhizophora mucronata made up 10% of wood used and people spent, on average, 22 hours per month collecting wood. The mean 24-hour CO concentration was 5.9ppm. The average level of PM2.5 during cooking was 10 mg/m 3 respectively. Chronic exposure at those levels is expected to cause significant health impacts of the kinds indicated by symptoms reported from the questionnaires. Improved cookstove introduction in Gazi is recommended as feasible as participants showed not only interest in improved cookstoves and awareness of the health implications from indoor air pollution, but also were willing to invest financially in improved cookstoves.